2020
DOI: 10.1002/emp2.12005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of new‐onset atrial fibrillation in geriatric trauma patients

Abstract: Introduction: Geriatric patients (age >65) comprise a growing segment of the trauma population. New-onset atrial fibrillation may occur after injury, complicating clinical management and resulting in significant morbidity and mortality. This study was undertaken to identify clinical and demographic factors associated with new-onset atrial fibrillation among geriatric trauma patients. Methods:In this case control study, eligible participants included admitted trauma patients age 65 and older who developed new-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…study by Marco et al 5 found an increase in new-onset AF after geriatric trauma, especially in male patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…study by Marco et al 5 found an increase in new-onset AF after geriatric trauma, especially in male patients.…”
Section: Discussionmentioning
confidence: 92%
“…4 Although our population is small, the occurrence of AF in our population is higher than the norm. This increase could be due to the patient’s trauma as a small study by Marco et al 5 found an increase in new-onset AF after geriatric trauma, especially in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diğer durumlarda atriyal fibrilasyonu önlemek için kullanılan ilaçlar travmaya neden olabilir. 65 Yaşlı travma hastalarının triajlarında "undertriaj"ın fazla yapıldığı görülmektedir. Yaşlı travma hastalarının triaj ve erken tedavisi için tüm travma sistemleri ve merkezlerinin yaşlı travma hastalarına özel protokollere sahip olması gerekmektedir.…”
Section: Elbi̇seleri̇n çIkarilmasi/çevreunclassified